The Factors That Helped in The Entry of British Investments into The Ottoman Sultanate 1272 AH / 1580- 1856 AD- 988 (Damascus University Journal of Historical Studies, 2022)
The internal and external factors in the Ottoman Sultanate, with the concomitant conclusion of Ottoman-European treaties since the sixteenth century, had a great impact on the disintegration of economic policies and the weakness of the Ottoman administration. In addition to that, the financial crises that the Sultanate went through and the state of weakness and weakness it reached, along with its willingness to fight the Crimean War 1269-1272 AH / 1853-1856 AD against Russia had a great impact on the penetration of European countries, especially Britain, thereby providing loans to the Ottoman Sultanate, and thus, external loans, along with internal and external factors, opened the Sultanate’s doors to start European investments, especially the British.
Keywords: Concessions; The Ottoman Sultanate; Treaties; British Investments